The public's reliance on satellite channels to receive news about the Corona epidemic: A field study on a sample of the audience of the capital, Baghdad - Mohammad, Ghazwan Jabbar (Al-Adab Journal, 2022)
The research aims to identify to which extent Iraqi people depend on satellite channels in following news of the emerging crisis of the Corona Virus Pandemic (Covid 19) that swept Iraq and the world, and since the news provided by satellite channels are the most convincing due to the fact that they are supported by audio and video materials, some satellite channels decided to shed the lights on real and unreal pieces of information related to the pandemic, such as rumors circulated in social media, and some satellite channels sought to refute them by hosting doctors through their programs and news bulletins.Our research raises a major question about the following: to which extent Iraqi people rely on satellite channels when it comes to receiving news and information related to the emerging Corona pandemic (Covid 19) instead of other media outlets and social media platforms. About the pandemic, to which extent satellite channels have succeeded in refuting rumors about the deadly vaccine, and its ability to urge people to take the vaccine.The researcher adopted the descriptive approach with the aim of discovering the facts, describing the phenomena accurately, and determining their characteristics qualitatively or quantitatively. Among the findings of the researcher:The people follow the news of the Corona pandemic through satellite channels, as it is a major source of information, as well as newspapers, radio stations and news websites.Half of the people sometimes follow the news of the Corona pandemic through social media.The Iraqi people prefer channels (the state-run television Al-Iraqiya satellite channel, Al-Arabiya satellite channel, and BBC Arabic) in following the news of the Corona pandemic, and it also depends on the Iraqi channels in the first place.One of the most important reasons for the people’s dependence on satellite channels alone in following the news of the Corona pandemic, (the speed of their transmission of news), (the transmission of news details) and (their credibility).